Integrity Identification in Ethnographic by Biopic of Kwee Tjie Hoei - Rustono Farady Marta (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2018)
This research will specifically trace the communication made by Kwee Tjie Hoei (A Hoei) or Karmaka Surjaudjaja which is manifest in the national film titled with "Love and Faith" which was released in 2015. This film is packed in the form of a romantic drama genre that tells the Biopic of A Hoei when building the business empire of PT OCBC NISP which at that time was in a crisis. The researcher is based on Communication Theory of Identity which was triggered by Michael Hecth and Aristotle's Rhetoric to probe the message conveyed in the film. The research paradigm is based on constructivism, while the method used in this research is HymesÂ’s Ethnographic of Speaking with eight components by the acronym of S-P-E-A-K-I-N-G and this type of research is descriptive with a qualitative approach. The unit of analysis used in the research was scenes in the film, so the researcher was able to identify Kwee Tjie HoeiÂ’s integrity which was shown in several stages of identity. The results showed that dominated the implicit message in the form of the integrity of Kwee Tjie Hoei's figure, in line with the principle of rhetoric that rests on the level of public communication.